Evaluasi Mutu Pelayanan Kefarmasian Berdasarkan Standar Pelayanan Minimal (Spm) Di Instalasi Farmasi - Teti Sutriyati Tuloli; Widy Susanti Abdulkadir; Nur Rasdianah (State University of Gorontalo, 2021)
Quality refers to compliance with predetermined standards or by requirements. The minimum service standard (MSS) in the health sector at the hospital is crucial because it is a measure of the hospital's performance of health services. This study was intended to describe the service quality in the pharmacy installation of Toto Hospital in Kabila based on four indicators of minimum pharmacy service standards, viz. drug waiting time for treatment completion, the absence of drug administration errors, customer satisfaction, and prescription writing according to the formulary. This descriptive cross-sectional research involved 154 outpatients and inpatients for the category of prescription writing according to the formulary and 154 outpatients for other categories as respondents as samples. Besides, the instruments were a customer satisfaction questionnaire and observation sheet. The results showed that the indicators of waiting time were nine minutes seven seconds and 18 minutes six seconds for concocted drug treatment; there was no error in administering drugs by 100%; customer satisfaction was 86.9%, and; prescription writing according to the formulary was 92.7%. . It was concluded that the Pharmacy Installation of Toto Hospital had not met the specified Minimum Service Standards (MSS).